2018
DOI: 10.1177/1043659618794256
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Care Practices of Mothers in Arab Societies: Implication for Infant Welfare

Abstract: It is important for nurses and midwives to be aware of traditional practices, cultural beliefs, and the implications for infant welfare if they are to effectively engage with families to promote the well-being of the newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 34 publications
1
16
0
4
Order By: Relevance
“…This suggests that while belief in the ‘evil eye’ is embedded in the folklore of Arab societies, as well as some Islamic societies (Abu‐Rabia , Arabiat et al. ), use of certain folk remedies which are not always a reflection of faith. Previous studies indicate that an amulet use is not limited to Arab culture as Turks (Kayabasi & Yanar ) and North Africa communities (Abu‐Rabia ) use amulets for similar reasons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that while belief in the ‘evil eye’ is embedded in the folklore of Arab societies, as well as some Islamic societies (Abu‐Rabia , Arabiat et al. ), use of certain folk remedies which are not always a reflection of faith. Previous studies indicate that an amulet use is not limited to Arab culture as Turks (Kayabasi & Yanar ) and North Africa communities (Abu‐Rabia ) use amulets for similar reasons.…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a larger qualitative study about health beliefs and folk models of illness among Arab families. Part 1 reported on analysis of immediate and early post‐partum care practices among Arab societies, and is published elsewhere (Arabiat et al., ). The study was commenced in June 2016, following obtaining institutional review board approval from the University of Jordan (ethics approval dated 26/5/2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that a person interested in folk remedies may use a complex system of traditional remedies mostly based on psychosocial interventions, mild herbs, ritualistic behaviour or household items. 2 , 3 The use of folk remedies to manage illness is often influenced by family beliefs and the natural or social environment they live in. 4 , 5 In this instance, understanding the relationship between health beliefs and traditional practices is important in conceptualising the capacity of families to manage illness during acute or chronic illness.…”
Section: Introductionmentioning
confidence: 99%